Parent and child perceptions of gambling promotions in Australian sport. (14th April 2019) - David, Jennifer L; Thomas, Samantha L; Randle, Melanie; Pitt, Hannah; Daube, Mike
Abstract: Gambling is recognized as a significant public health problem. However, there is little research exploring community attitudes towards gambling and the development of advocacy initiatives. Engaging adults and young people in advocacy efforts is recognized as being beneficial to the successful implementation of harm prevention and reduction strategies. This study explored the attitudes of young people and their parents towards the alignment of gambling with sport, and the strategies they perceive could be used to prevent and reduce gambling related harm. Using a Constructivist Grounded Theory approach, 30 family groups from Melbourne, Australia participated in semi-structured interviews. Parents and young people were asked about gambling and its promotion, alignment with sporting codes, the potential impact on young people and strategies that may prevent or reduce gambling harm. Thematic analysis was undertaken to interpret the data. The sample comprised 29 parents, one grandparent and 48 young people. Themes emerging from the data related to the use of imagery and appeal strategies in advertisements, the normalization of betting in advertisements and the alignment of betting with sport. Parents and young people also identified a number of potential gambling harm prevention and reduction initiatives. Parents and young people were able to describe a range of strategies used by gambling companies to promote their products, understand the potential impact of these strategies, and recommend strategies to reduce harm. Given this level of understanding there is clearly an opportunity to engage young people and stakeholders in advocacy initiatives aimed at reducing and preventing gambling harm.